2023
DOI: 10.1080/14786419.2023.2177993
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel benzoxazole/chromene-phthalide scaffolds hybrids as potential natural products-based fungicide

Abstract: Phthalide, benzoxazole, and chromene are important heterocyclic skeletons with extensive biological activities. In order to develop novel potential antifungal agents, twenty-two benzoxazole/chromene-containing phthalide derivatives were prepared, and their fungicidal activity against nine common plants pathogenic fungi were evaluated in vitro. The EC 50 values indicated that compound Z-4b displayed superior antifungal activity against P. oryzae (11.0 μg/mL), F. solani (8.5 μg/mL), P. capsici (27.8 μg/mL), V. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the previous study, we found that 3-n-butylphthalide (NBP), an active ingredient derived from celery seed and capable of treating ischemic stroke, had potential antifungal potency against phytopathogenic fungi. [3][4][5][6] Thus, it can serve as a precursor for the development of new botanical fungicide. Moreover, among the family of fivemembered nitrogen/oxygen-containing aromatic heterocycles, 1,3,4-oxadiazole and 1,2,4-triazole scaffolds are widely present in pharmaceutical or pesticide molecules, and exhibited a pronounced diversity of biological activities due to their ability to form interactions with various enzymes, proteins, and receptors in organisms, [7][8][9] such as anticancer, [10,11] antiviral, [12,13] antibacterial, [14][15][16] antifungal, [17][18][19] and herbicidal [20] activities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we found that 3-n-butylphthalide (NBP), an active ingredient derived from celery seed and capable of treating ischemic stroke, had potential antifungal potency against phytopathogenic fungi. [3][4][5][6] Thus, it can serve as a precursor for the development of new botanical fungicide. Moreover, among the family of fivemembered nitrogen/oxygen-containing aromatic heterocycles, 1,3,4-oxadiazole and 1,2,4-triazole scaffolds are widely present in pharmaceutical or pesticide molecules, and exhibited a pronounced diversity of biological activities due to their ability to form interactions with various enzymes, proteins, and receptors in organisms, [7][8][9] such as anticancer, [10,11] antiviral, [12,13] antibacterial, [14][15][16] antifungal, [17][18][19] and herbicidal [20] activities (Figure 1).…”
Section: Introductionmentioning
confidence: 99%